Delineating the Genetic Variability and Diversity in Green Gram [Vigna radiata (L.) Wilczek] Genotypes - Mahla, Prachi; Ram, Manohar; Beniwal, Jogender; Nehra, Anju; Dalip; Chawla, Rukoo (International Journal of Bio-resource and Stress Management, 2024)
This study evaluated 44 green gram genotypes collected from the AICRP on MULLaRP to investigate genetic variability and divergence. During kharif (July–October, 2020), the genotypes were assessed for various morphological traits. The phenotypic coefficient of variation was higher than the genotypic coefficient of variation, indicating significant variability. Clusters plant-1, pods plant-1, and seed yield plant-1 exhibited the highest genetic and phenotypic coefficient of variation. High heritability was observed for 1000-seed weight, clusters plant-1, pods plant-1, and seeds pod-1, suggesting the influence of additive genetic factors. Genetic advance as a % of the mean was particularly notable for clusters plant-1, pods plant-1, and seed yield plant-1. Further analysis using Mahalanobis D2 statistics resulted in the classification of genotypes into seven clusters, with Cluster I being the largest. Cluster IV and VI showed the highest inter-cluster distance, indicating substantial genetic divergence. Notably, Cluster III represented by AKM 1801 displayed superior characteristics such as high mean values for pod length, seeds pod-1, 1000-seed weight, and seed yield per plant, making it a potential candidate for green gram improvement programs. In terms of genetic diversity, 1000-seed weight contributed the most, followed by clusters plant-1 and chlorophyll content. These findings highlight the importance of these traits in shaping the genetic diversity observed among the green gram genotypes.